2015
DOI: 10.1016/j.juro.2015.03.091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Duloxetine on Urethral Continence Reflex and Bladder Activity in Rats with Cerebral Infarction

Abstract: Purpose: We investigated the effect of duloxetine, a norepinephrine and serotonin reuptake inhibitor, on the sneeze induced continence reflex and on bladder function in rats with cerebral infarction. Materials and Methods: Using urethane anesthesia the effect of duloxetine (1 mg/kg intravenously) on the amplitude of urethral responses during sneezing as well as urethral baseline pressure at the mid urethra was evaluated in normal female adult rats and cerebral infarction rats. Tilt leak point pressure was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…Eight normal and eight VD rats were used. The tilt LPP was measured with rats in an upright position, as previously reported . Briefly, the intravesical pressure was elevated gradually by raising a saline reservoir with Evans blue (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight normal and eight VD rats were used. The tilt LPP was measured with rats in an upright position, as previously reported . Briefly, the intravesical pressure was elevated gradually by raising a saline reservoir with Evans blue (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The tilt LPP was measured with rats in an upright position, as previously reported. 14,15 Briefly, the intravesical pressure was elevated gradually by raising a saline reservoir with Evans blue (100 μg/mL). LPP was defined as the lowest pressure at which blue-color saline leaked from the urethral meatus.…”
Section: Experiments 3: Effects Of Tramadol (Iv) On the Tilt Leak mentioning
confidence: 99%
“…ISs are known as inducing not only bladder overactivity, but also stress urinary incontinence [100]. After IS occurrence duloxetine, a norepinephrine and serotonin reuptake inhibitor reduced bladder overactivity but failed to enhance active urethral closure mechanisms during sneezing, suggesting that disorganization of the brain network after IS might influence the effect of duloxetine on lower urinary tract function.…”
Section: Adult Neurogenesis In Ischemic Strokementioning
confidence: 99%
“…Researches are currently underway in order to develop new neurogenic bladder treatments, and some researchers have reported that nerve stimulation and stem cells improve neurogenic bladder [5-7]. In order to effectively treat neurogenically dysfunctional bladder, treatments should also prevent functional deterioration of the central nervous system.…”
mentioning
confidence: 99%